Effects of 12-Week Multivitamin Supplementation on Serum Folate Levels in Pre-Menopausal Females. (29th May 2020) - Osburn, Shelby; Roberson, Paul; Medler, Jessica; Shake, Jacob; Arnold, Robert; Alamdari, Nima; Bucci, Luke; Vance, Arianne; Sharafi, Mastaneh; Young, Kaelin; Roberts, Michael
Abstract: Objectives: We determined if multivitamin supplementation (MV) affected serum folate levels in women during a 12-week intervention, and if genotypes affected these outcomes. Methods: Women (21–40 years old) were recruited from the local community. PRE testing occurred between 0600–0900 AM 5 ± 2 days following each participants' last menstrual cycle, and involved a buccal cell collection and a fasted blood draw. Participants were then randomly assigned in a double-blinded fashion to the MV group (n = 43) or placebo group (n = 51). MV (per 2 beadlets-in-capsule serving) contained 50 mcg vitamin D3, 6.7 mg alpha tocopherol of vitamin E as mixed tocopherols, 90 μg vitamin K2 MK7, 600 μg 5-methyltetrahydrofolate, 8 μg B12, 8 mg iron, 50 mg magnesium, 1 mg boron, and 320 mg omega-3 fatty acids. The placebo capsules contained safflower oil and cellulose. Participants consumed two capsules per day with breakfast for 12 weeks. Following the intervention, participants reported to the laboratory for POST testing. Serum folate analyses were performed at a hematology laboratory (East Alabama Medical Center, Opelika, AL, USA). SNPs related to folate metabolism (MTHFR rs1801133, MTHFR rs1801131, MTHFR rs2274976, MTRR rs1801394) were interrogated using the Axiom PMDA.r6 array (Thermo Fisher Scientific, Waltham, MA, USA). Results: A group × time interaction was observed for serum folate levels and dietary folate intake ( P  < 0.001). MV supplementation increased serum folate levels from PRE to POST ( P  < 0.001), whereas no change occurred in the placebo group ( P  = 0.345). MV supplementation also increased the PRE to POST intakes of folate ( P  < 0.001), whereas these values were not affected in the placebo group ( P  = 0.576). MV supplementation increased serum folate levels regardless of MTHFR genotype. The MTRR rs1801394 genotype showed a genotype x time interaction ( P  = 0.049); specifically, folate levels increased in the AG and AA genotypes ( P  < 0.05), but not the GG genotype ( P  = 0.080). Conclusions: MV supplementation increases serum folate levels. While the interrogated MTRR genotype may play a role regarding the efficacy of MV supplementation, these data are preliminary given the limited n-size. Funding Sources: Funding was provided to MDR, RRA, and KCY by Ritual, Inc. Support was also provided by The GHT Companies, and Kappa BioSciences.